2006
DOI: 10.1105/tpc.106.042424
|View full text |Cite
|
Sign up to set email alerts
|

Functional Replacement of Ferredoxin by a Cyanobacterial Flavodoxin in Tobacco Confers Broad-Range Stress Tolerance

Abstract: Chloroplast ferredoxin (Fd) plays a pivotal role in plant cell metabolism by delivering reducing equivalents to various essential oxidoreductive pathways. Fd levels decrease under adverse environmental conditions in many microorganisms, including cyanobacteria, which share a common ancestor with chloroplasts. Conversely, stress situations induce the synthesis of flavodoxin (Fld), an electron carrier flavoprotein not found in plants, which can efficiently replace Fd in most electron transfer processes. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
257
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(275 citation statements)
references
References 50 publications
18
257
0
Order By: Relevance
“…We have introduced the Fld gene from the cyanobacterium Anabaena PCC7119 into the genome of tobacco and demonstrated that transgenic plants expressing this flavoprotein in chloroplasts developed generalized tolerance to various sources of oxidative and environmental stress (26). Here we show that these transformants were also able to grow on Fe-limited substrates.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…We have introduced the Fld gene from the cyanobacterium Anabaena PCC7119 into the genome of tobacco and demonstrated that transgenic plants expressing this flavoprotein in chloroplasts developed generalized tolerance to various sources of oxidative and environmental stress (26). Here we show that these transformants were also able to grow on Fe-limited substrates.…”
mentioning
confidence: 83%
“…We therefore analyzed the response to Fe limitation of transgenic tobacco plants in which Fld accumulated in plastids (pfld lines, for plastidic Fld) using WT siblings and transformants expressing the flavoprotein in the cytosol (cfld lines, for cytosolic Fld) as controls. Preparation of stable homozygous pfld and cfld tobacco lines expressing various levels of Fld has been described elsewhere (26). Most experiments were carried out with plants from lines pfld5-8, pfld4-2, and cfld1-4, containing Fld at 70, 57, and 108 pmol⅐g Ϫ1 fresh weight, quantities comparable to 98 pmol⅐g Ϫ1 fresh weight for endogenous Fd (26).…”
Section: Transgenic Plants Expressing a Plastid-targeted Fld Displaymentioning
confidence: 99%
See 2 more Smart Citations
“…These crops and others under development show overexpression of bacterial RNA chaperones (Castiglioni et al 2008), and NF-Y class transcriptional regulators (Nelson et al 2007) in which drought tolerance is reported. Tolerance to a whole range of stresses in plants may also be induced by RNA silencing to downregulate poly ADP ribose polymerase (Vanderauwera et al 2007), and overexpression of a cyanobacterial flavodoxin (Tognetti et al 2006). Until comprehensive field trials are conducted with this material, some caution must be exercised.…”
mentioning
confidence: 99%